Efficacy of hepatitis C virus eradication after curative treatment for hepatocellular carcinoma in patients with advanced hepatocellular carcinoma and decreased hepatic functional reserve: A nationwide, multicentre study by the Japanese Red Cross Liver Study Group. Issue 7 (18th May 2022) - Mashiba, Toshie; Joko, Kouji; Kurosaki, Masayuki; Ochi, Hironori; Marusawa, Hiroyuki; Uchida, Yasushi; Fujii, Hideki; Kojima, Yuji; Yoshida, Hideo; Goto, Tohru; Akahane, Takehiro; Kondo, Masahiko; et al.
Abstract: Improvements in the hepatocellular carcinoma (HCC) recurrence rate and survival have been frequently reported following virus eradication after hepatitis C virus (HCV)‐related HCC cure. However, the efficacy of direct‐acting antiviral (DAA) therapy in patients who included those with advanced HCC and decreased hepatic functional reserve is unknown. A comparative examination was retrospectively conducted of 141 patients with hepatitis C who started DAA therapy within 1 year after undergoing curative HCC treatment and showed a sustained viral response (SVR) and 327 patients who underwent curative treatment for HCV‐related HCC and did not subsequently receive antiviral therapy. Whether DAA therapy was given was identified as an independent factor related to both HCC recurrence and survival. Both the recurrence and survival rates improved significantly with DAA therapy in Child‐Pugh (CP)‐A, whereas no difference in the recurrence rate was seen with DAA therapy in CP‐B. However, the survival rate was significantly higher in the DAA group in this class. Similarly, dividing the patients by the Milan criteria showed significant improvements in the recurrence rate and survival with DAA therapy in patients within the Milan criteria. Patients with HCC beyond the Milan criteria showed no difference in recurrence rates, but the DAA group tended to have higher survival rates. Thus, DAA after curative therapy for HCC can be expected to improve survival in patients with advanced HCC or decreased hepatic functional reserve. HCV should be aggressively eradicated in all patients eligible for curative treatment of HCC.